Metal halide perovskite materials in photocatalysis: Design strategies and applications - Chen, Zhen-Yu; Huang, Ning-Yu; Xu, Qiang (Coordination chemistry reviews, 2023)
In this review, we firstly overview the photocatalytic fundamentals, crystal structures, coordination environments and characteristics of metal halide perovskite (MHP) photocatalysts. Then, the novel strategies for MHP photocatalyst design, such as morphology regulation, heterojunction construction, surface/interface modification and material encapsulation are summarized. Additionally, advanced progresses for MHPs in hydrogen evolution, carbon dioxide reduction, organics degradation and nitric oxide removal are introduced. In the end, the current challenges and outlooks of MHP photocatalysts in environment and energy are presented. [Display omitted] •Fundamentals, crystal structures, coordination environments and characteristics of metal halide perovskite photocatalysts for photocatalysis are introduced.•Universal strategies for boosting the photocatalytic activity and stability of metal halide perovskites are summarized.•Advanced progresses for metal halide perovskites in photocatalytic H2 evolution, CO2 reduction, organics degradation and NO removal are presented.•Challenges and prospects of metal halide perovskite photocatalysts in environment and energy are discussed. Photocatalytic technologies have been widely considered as ideal ways to deal with the energy shortage and environmental crisis. Metal halide perovskites (MHPs) are recognized as a new generation of photocatalysts on account of their tunable band gap, low binding energy, wide visible-light absorption range, high photoluminescence quantum yield and fast carrier transfer. However, the development of efficient MHP photocatalysts has also encountered challenges. MHPs with ionic crystal structures are difficult to stabilize under water, oxygen atmosphere and high temperatures, as well as the serious recombination of photogenerated electrons-holes and weak oxidation activity during photocatalysis. Herein, we overview recent advances and developments for MHPs in photocatalysis, including H2 evolution, CO2 reduction, organic pollutant degradation and NO removal. In the beginning, the photocatalytic fundamentals, crystal structures, coordination environments and characteristics of MHP photocatalysts have been discussed. In order to overcome the severe charge recombination, poor stability and lack of active sites of MHPs, various design strategies for efficient MHP photocatalysts are presented, such as morphology regulation, heterojunction construction, surface/interface modification and material encapsulation. In the end, the current challenges and outlooks of MHP photocatalysts are provided to highlight the glorious future and significant position of MHP materials for photocatalytic applications.